ANALISIS PROKSIMAT TEPUNG HASIL PROSES EKSTRAKSI MINYAK DARI PUREE IKAN [The Proximate Analysis of Powdered of Extraction Processed Results From Fish Puree] - Djumhawan R. Permana; Padmono Citroreksoko (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2003)
The aim of these research were separation of oils from the fish puree on fish powdered and then proximate analysis of the puree or defatted powdered, which were protein, carbohydrate, lipid, water, ash contents and also the performance of the powdered fish. The results showed that the puree or defatted powdered have 7.42-14.43% of lipids and 51.70-77.00% of water contents. On the other hands, if fish puree and the extracted fish powdered were dried, resulted increasing oil content about 29.87-44.07% of the powdered, which were colour performance from white to brownish or brown. The high protein contents (93.26-96,84%) of the white fish powdered could be substituted or added to milk pow'der to getting a certain protein contents. The other hand the brow'nish or brown fish powdered have 90.35-91.84% of protein, could be for animals feed in the certain protein content. The content of carbohydrates were low for the white fish powdered of puree or the oil extracted powdered, but increasing of carbohydrates contents in the brown or brown fish powdered of the oil extracted powdered. The ash contents of all samples of the powders were low, because the puree or the oil extracted powdered without the bones or the head parts oh the fishes. The water contents of the oil extracted powdered of brown puree (as wet performance) have the highest of water contents about 77.00% compared with other treatments.AbstrakPenelitian ini bertujuan untuk memisahkan minyak dari puree atau tepung ikan dari ikan Sardinella, dan dilakukan analisis proksimat untuk mengetahui kandungan protein, karbohidrat, lemak, kadar air, abu serta penampilan tepung yang dihasilkan. Hasil penelitian menunjukkan bahwa puree maupun ampasnya mempunyai kandungan minyak antara 7,42-14,43%, dan kadar air 51,7077,00%. Namun apabila puree dan ampas-ampasnya setelah diambil minyaknya dan dikeringkan, maka kandungan minyaknya meningkat menjadi 29,87-44,07% yang menghasilkan tepung ikan dengan penampilan mulai warna putih sampai eoklat tua. Kadar protein yang sangat tinggi (93,26-96,84%) dari tepung ikan yang berwarna putih memungkinkan tepung ini digunakan sebagai substitusi atau pencampur susu serbuk dengan kadar protein tertentu. Sedangkan tepung ikan yang memiliki kadar protein 90,3591,84% berwarna coklat, dapat digunakan sebagai sumber protein untuk pakan ternak sesuai dengan kebutuhan kadar protein tertentu. Kadar karbohidrat relatif sangat rendah pada puree maupun ampas puree yang berwarna putih. Namun ampas puree yang berwarna coklat mengandung kadar karbohidrat lebih tinggi. Kadar abunya relatif sangat rendah, karena paree maupun ainpas puree ikan tidak mengandung tulang ikan maupun bagian kepala dari ikan yang telah dibuat puree. Kadar air pada ampas puree yang berwarna coklat tua (penampilan basah) memiliki kadar air tertinggi yaitu 77,00% dibandingkan dengan perlakukan lainnya.